Pengaruh Metode Problem Based Learning Pada Materi Redoks Di Kelas X SMA Negeri 1 Wori - Regina Mongi; Meytij J Rampe; Septiany Ch Palilingan (Oxygenius Journal Of Chemistry Education, 2019)
The purpose of this study, to determine whether there are differences in student learning outcomes in using the Problem Based Learning method with the lecture method. During approximately 1 month different methods were applied in 2 classes, namely the Problem Based Learning class and the Lecture class with a total of 25 students each, then to see the learning outcomes a post-test was conducted. The results showed the value of t arithmetic = 2.92> t table 2.010, so that the conclusion Ha is accepted and H0 is rejected, it means there are differences in student learning outcomes using the Problem Based Learning method with those using the lecture method on redox material.